On the intensifying of foreign language teaching to undergraduates of technical specialization - Ruslan N. Abitov; Rais S. Safin; Evgeny A. Korchagin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2018)
The article deals with the intensifying of foreign language teaching to undergraduates of technical specialization. The reduction of guided hours of teaching foreign languages, triggered by the transition to new Federal Educational Standards, is revealed. The notion of the intensifying of foreign language teaching to undergraduates is analyzed. The correspondence between two-level competences, presented in Federal Educational Standards, and ones, developed by language pedagogy scholars, is defined. The notions of “standard guided hours”, “teaching efficiency quotient”, “recommended guided hours” are introduced. The components of model of intensifying of foreign language teaching are revealed. The results of an experiment are given.